Secarik Harap di Balik Mimpi: Menuju Terwujudnya Zero Waste di Desa Bahalayung Kabupaten Barito Kuala - Alhadi, Syarifah Soraya; Hamid, Ismar; Khairussalam, Khairussalam; Dewi, Dewi; Liani, Sava'ah Intan; Dila, Ratna; Jumiati, Jumiati; Anshari, Ahmad (Prodi Sosiologi FISIP ULM, 2024)
The issue of waste in Bahalayung Village, Bakumpai Sub-district, Barito Kuala Regency, which is located on the banks of the Nagara River, is still a serious problem that needs to be resolved because it affects various aspects of community life. Until now, the handling of the waste problem has not been clearly seen in the village, so the service team implemented the “Waste-Free Bahalayung Village” program as a solution. The community development program is implemented through a community empowerment approach. The team tried to encourage the awareness of the government and the people of Bahalayung Village to pay attention to environmental cleanliness and always come up with initiatives to maintain environmental sustainability. This program includes enabling and empowering, which is then elaborated through various activities, namely: 1) Establishment and provision of waste bank facilities; 2) Waste management through production houses; 3) Nature school; 4) Environmental action; 5) Distribution of environmental awareness questionnaires and community skills and, 6) Village discussions. The implementation of the program was supported by the live-in method in the village for 37 days, which took place from July 16 to August 21, 2023. The results achieved from the implementation of this service program are changes in the community's perspective on waste and increased community concern for the cleanliness of the village environment. Through this program, the team believes that the government and community of Bahalayung Village will pay more attention to the waste problem and come up with sustainable initiatives in dealing with it. The implication is that Bahalayung Village will move gradually towards the realization of a zero waste village.